Isolation of attosecond pulses from the attosecond lighthouse. (16th December 2016) - Hammond, TJ; Balogh, Emeric; Kim, Kyung Taec
Abstract: This paper proposes and verifies methods to improve the isolation of the attosecond pulses generated via the attosecond lighthouse technique in gases. We find that the converging fundamental field can compensate for the inherent diverging wavefront of the attosecond pulses, but is only valid over a limited portion of the spectrum and sacrifices the maximum attainable photon energy. We discuss two methods of manipulating the fundamental field to control the divergence of the attosecond pulses: the first method uses a perturbing beam that manipulates the wavefront, and the second method controls the fundamental dispersion. These methods improve the isolation of the attosecond pulses up to the cutoff photon energy.